2012
DOI: 10.1002/jsfa.5775
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electroporation on viability and bioconversion of isoflavones in mannitol‐soymilk fermented by lactobacilli and bifidobacteria

Abstract: Application of electroporation on lactobacilli and bifidobacteria could be beneficial for the development of fermented soymilk with enhanced bioactivity. Considering the enhanced bioactive aglycones, this soymilk could be useful for the prevention of hormone-dependent disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Experimental studies suggest that lipid peroxidation could present a mechanism of the long-lived cell membrane permeability, which persists for minutes after exposing the cells to electric pulses [20][21][22][23][24][25][26][27][28][29][30][31][32]. The aim of our study is to investigate whether peroxidized lesions in the cell membrane could be permeable enough to account for the post-pulse membrane permeability and conductance measured in electropermeabilized cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies suggest that lipid peroxidation could present a mechanism of the long-lived cell membrane permeability, which persists for minutes after exposing the cells to electric pulses [20][21][22][23][24][25][26][27][28][29][30][31][32]. The aim of our study is to investigate whether peroxidized lesions in the cell membrane could be permeable enough to account for the post-pulse membrane permeability and conductance measured in electropermeabilized cells.…”
Section: Discussionmentioning
confidence: 99%
“…The complete resealing of the cell membrane takes several minutes at room temperature [15][16][17], which is about 8−9 orders of magnitude longer than the time of electropore closure as reported from MD investigations [18,19]. Experimental studies suggest that a possible alternative mechanism to explain the observed long-lived permeability of cell membranes is lipid peroxidation [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the pores in the cell wall, particularly in the peptidoglycan wall of Gram-positive bacteria, are much more stable and can be visualized under an electron microscope [16] (Figure 2). …”
Section: Membrane Levelmentioning
confidence: 99%
“…Scanning electron micrographs show Lactobacillus casei bacteria before (A) and after (B) exposure to an electric field pulse of 7.5 kV/cm amplitude and 4 ms duration. Reprinted, with permission from[16]. Scale bar, 2 mm.…”
mentioning
confidence: 99%